To Problem Concerning Calculation of Generalized Indices at Thermal Power Station - V. I. Nazarov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2007)
The paper contains expressions for calculation of specific fuel consumption rate in respect of electric and thermal power that reliably characterize thermodynamic efficiency of generating equipment operation.